(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
As the global business landscape continues to evolve, the integration of advanced technologies has become imperative for enhancing efficiency and competitiveness. This paper explores the multifaceted role of Artificial Intelligence (AI) in revolutionizing supply chain management (SCM). The traditional supply chain paradigm is being reshaped by AI-driven solutions, presenting opportunities for optimization, agility, and resilience. The author conducted a systematic literature review evaluation of the published literature from peer-reviewed journals in the major databases Scopus and Web of Science. The analysis of literature is a frequency analysis of the literature by considering the year of publications, the contribution of leading journals and publishers, and the methodology adopted and the content analysis of literature. The author’s findings from the literature reveal that key AI applications in supply chain management, such as demand forecasting, inventory management, logistics optimization, and risk mitigation enable organizations to make informed decisions, reduce forecasting errors, and optimize inventory levels, ultimately improving overall supply chain efficiency.